ЛИНГВИСТИК КОМПЕТЕНЦИЯНИ ШАКЛЛАНТИРИШДА АМАЛ ҚИЛИНАДИГАН Принциплар - Тажбенова, С.С. (SCIENCE and SOCIETY, 2024)
This article highlights the theoretical foundations of scientific research aimed at the formation of literacy, speech culture, linguistic competence, and the nature of linguistic competence of students in primary school mother tongue classes.
Keywords: cognition; punctuation; sound; structural-semantic; extralinguistic; functional; comparative analysis; phonetics; lexicology; word formation; morphology; syntax; stylistics; positional changes; phoneme; letter